2020
DOI: 10.7150/jca.41090
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Epcam and CD133 Correlates with Poor Prognosis in Dual-phenotype Hepatocellular Carcinoma

Abstract: Background: Dual-phenotype hepatocellular carcinoma (DPHCC) is associated with high rate of post-operative recurrence and low rate of survival, which may reflect the post-operative persistence of cancer stem cells (CSCs). Here we explored the potential correlation between DPHCC and expression of CSCs markers. Methods: In this retrospective study, we included 19 patients with DPHCC and 61 patients with non-DPHCC treated in 2015 by liver resection. Paraffin-embedded tumor tissue specimens were analyzed using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Different from CHC, dual-phenotype hepatocellular carcinoma (DPHCC) is a new subtype of HCC 7 . Previously, we found that DPHCC had a higher rate of postoperative recurrence and a lower survival rate than non-DPHCC 8 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Different from CHC, dual-phenotype hepatocellular carcinoma (DPHCC) is a new subtype of HCC 7 . Previously, we found that DPHCC had a higher rate of postoperative recurrence and a lower survival rate than non-DPHCC 8 .…”
Section: Introductionmentioning
confidence: 86%
“…The pathological diagnosis of DPHCC is: (1) Immunohistochemically, more than 15% of the tumor cells, at least one hepatocyte marker (such as Hep Par 1) shows strong positive expression, and mainly diffuse distribution; (2) More than 15% of tumor cells, at least one cholangiocyte marker (such as CK19), and at least one hepatocyte marker (such as Hep par 1) are co-expressed. If the tumor tissue contains any component of HCC and intrahepatic cholangiocarcinoma, no matter whether there is a transition zone between these components or the tissue shows that tumor cells do not express markers of both hepatocytes and cholangiocarcinoma, these patients cannot be diagnosed as DPHCC 7 , 8 . While the incidence rate of DPHCC is much lower than that of CHC 9 , DPHCC is more aggressive and exhibits a worse postoperative prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, CD133 expression is negatively correlated with overall survival and recurrence rates in patients with HCC [ 144 , 236 , 237 , 238 ]. HCC patients with higher level of CD133 expression in primary lesion have shorter 5-year survival times and higher relapse rates after surgical resection compared to patients with lower CD133 expression [ 144 , 239 ]. The up-regulated expression levels of CD133 have also been related to the ability to survive under hypoxia or malnutrition by performing autophagy [ 240 ].…”
Section: Potential Clinical Application Of Liver Cancer Stem Cellsmentioning
confidence: 97%
“…These authors found that the CD133-positive subpopulation showed a distinct high tumorigenicity in an immunodeficiency mouse xenograft model and lower levels of mature hepatocyte-specific markers, such as cytochrome P450 and glutamine synthetase (GS), when compared with CD133-negative counterparts [ 143 ]. Furthermore, Zhang et al found that enhanced cytoplasmic CD133 expression is correlated with poor prognosis HCC patients [ 144 ]. Interestingly, normal stem/progenitor cells and CSCs share many features, including the capacity to self-renew and differentiate into multiple cell types [ 145 ].…”
Section: Surface Marker-based Therapiesmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) has a high mortality among all cancers worldwide[ 1 ]. Most patients with HCC have decreased liver function and require treatment to completely excise the lesion and effectively mitigate further damage to the liver[ 2 ].…”
Section: Introductionmentioning
confidence: 99%